Proposta de um modelo elétrico simplificado e um modelo elétrico dinâmico de eletrolisadores para eletrônica de potência aplicada em sistemas de produção de H2V - Sousa, Humberto Pontes Van Ool de (2025)
This work proposes the development of a dynamic electrical model capable of representing the electrical characteristics of electrolytic cells over a wide operating range, with applicability in the analysis of intermittency of renewable energy sources, in the sizing of new power electronic converter topologies, and in control systems. Initially, a literature review on the fundamentals of water electrolysis and the main water electrolysis technologies was conducted. The integration of electrolysis systems with renewable energy sources was discussed, emphasizing the role of power electronics in reducing the impact of the inherent intermittency of some renewable sources. After the theoretical foundation, a simplified electrical model of a bipolar alkaline electrolyzer was developed. The simplified electrical model was experimentally validated, and a buck converter was sized using the simplified electrical model as the load, demonstrating low voltage and current ripple on the load. Subsequently, a dynamic electrical model for electrolytic cells, capable of representing the temporal behavior over a wide operating range, was proposed based on the analysis of electrical models found in the literature. The dynamic electrical model was proposed for an alkaline cell and experimentally validated, demonstrating greater accuracy in steady-state and power variation conditions compared to the other electrical models analyzed. The results obtained demonstrated that the proposed dynamic electrical model is a tool capable of analyzing the intermittency of renewable energy sources and optimizing the sizing of converters and control systems in green hydrogen production systems.